DINAMIKA PERKEMBANGAN INDUSTRI KERAJINAN TENUN TROSO DI JEPARA - Alamsyah, Alamsyah (Faculty of Humanities, Diponegoro University, 2014)
Troso Weaving is a craft industry which has a long existence. This weaving become an economic support for Troso people’s life and the surrounding communities. At the beginning, the industry existence just become a side activity of the communities, which then develop into economic foundation of the communities. It shows that Troso Weaving has given an economic contribution for most of the communities. Through this industry, the communities’ economic activity is more dynamic. From this activity, there are hundreds enterpreneurs and craftsmen born and even thousands workers rely on their life in this sector. Thus, this industry has develop rapidly and become one of Jepara District economic icon.